PENYULUHAN DAN PELAYANAN KESEHATAN PADA TK IT BAITUL IZZAH, KOTAMADYA BENGKULU, PROVINSI BENGKULU - Maria Eka PY; Ichsana Pranatawati; Sri Yunita (DHARMA RAFLESIA, 2017)
Blood group is not only as a complement of identity card, but also is required in emergency, such as in accident where people need blood transfusion. Additionally, bloodgroup is important to know due to the fact that there are some genetic disorders caused byblood type. Golden age of a kid is under two years old. However, stunting at a kid underfive years old can cause many growth disorders, including cognitive and motor growth.Therefore, nutrition intake in food is important to be concerned in order to optimize thekid’s growth. Baitul Izzah was one of Integrated Islamic (IT) kindergartens in BengkuluCity. This school had three A Classes, one Pre-School Class (PAUD), and nine B Classesin which each of them consisted of twenty five pupils and two teachers. The objective ofthis dedication is to know the pupils’ nutritional status at the school so that parents canknow their kid’s growth. Besides, this dedication aims to give counseling about how towash hands correctly in which we know that washing hands before eating or after doingactivities will decrease the risk of communicable diseases like wormy disease andinfluenza. This activity was accomplished on August 16, 2014. It was followed by twoclasses at Kindergarten B which consisted of 46 pupils and accompanied by the class teacher. Based on IMT (Body Mass Index), it was found that there were 18 pupils withnormal nutritional status, 19 pupils were obesity, 2 pupils were underweight and 7 pupilswere overweight. From the blood group checkup, it was found that all of the pupils hadrhesus + with various blood groups. Furthermore, the counseling about how to washhands correctly and good foods was accomplished. From the counseling, it was found thatthe pupils of the kindergarten were very enthusiastic. Following the counseling, directpractice about washing hands correctly was also conducted as well as giving nutritionalfood like mung bean porridge and milk, and souvenirs to the school at the end. Keywords: Nutritional Status, Blood Type, Washing Hands Correctly, Kindergarten